Pandora's Box: Corporate Power, Free Trade, and Canadian Education - Axelrod, Paul (Labour / Le Travail, 1995)
The article reviews the book, "Pandora's Box: Corporate Power, Free Trade, and Canadian Education," by John Calvert.
Keywords: BOOKS -- Reviews; CALVERT, John; Free trade; Nonfiction; PANDORA'S Box: Corporate Power, Free Trade & Canadian Education (Book)